Handbook of research on discourse behavior and digital communication : language structures and social interaction - Taiwo, Olurotimi Adebowale. (Information Science Reference, 2010)
"This book provides a variety of chapters on discourse behavior in digital communication, including computer-mediated communication as well as aspects of behavior typically associated with online discourse like cyberbullying"--Provided by publisher.